The Elusive Red Sea: Sacred Geography, Philology, and the Crisis of Biblical Scholarship in the Age of Enlightenment - Groetsch, Ulrich (Church history and religious culture, 2025)
The story of the biblical Exodus has fascinated scholars and the public alike. Whereas the theological and cultural implications of the successful rescue of the Jewish people from slavery are undisputed, biblical scholars and archaeologists still debate the historical validity of the events. During the sixteenth and seventeenth centuries, early modern scholars engaged in passionate debates about the exact location of the biblical Red Sea. Relying exclusively on philological tools, these scholars often produced adventurous theories to address problems inherent in the storyline. At the same time, however, this body of scholarly literature provided fuels for Enlightenment radicals in their attacks on Scripture. With the philological debates of the early modern period at an impasse, scholarship increasingly resorted to the adage “seeing is believing,” ushering in the era of biblical archaeology and exploration.